Effects of nurse staffing, work environments, and education on patient mortality: An observational study - Cho, Eunhee; Sloane, Douglas M.; Kim, Eun-Young; Kim, Sera; Choi, Miyoung; Yoo, Il Young; Lee, Hye Sun; Aiken, Linda H. (International journal of nursing studies, 2015)
While considerable evidence has been produced showing a link between nursing characteristics and patient outcomes in the U.S. and Europe, little is known about whether similar associations are present in South Korea. To examine the effects of nurse staffing, work environment, and education on patient mortality. This study linked hospital facility data with staff nurse survey data (N=1024) and surgical patient discharge data (N=76,036) from 14 high-technology teaching hospitals with 700 or more beds in South Korea, collected between January 1, 2008 and December 31, 2008. Logistic regression models that corrected for the clustering of patients in hospitals were used to estimate the effects of the three nursing characteristics on risk-adjusted patient mortality within 30 days of admission. Risk-adjusted models reveal that nurse staffing, nurse work environments, and nurse education were significantly associated with patient mortality (OR 1.05, 95% CI 1.00–1.10; OR 0.52, 95% CI 0.31–0.88; and OR 0.91, CI 0.83–0.99; respectively). These odds ratios imply that each additional patient per nurse is associated with an 5% increase in the odds of patient death within 30 days of admission, that the odds of patient mortality are nearly 50% lower in the hospitals with better nurse work environments than in hospitals with mixed or poor nurse work environments, and that each 10% increase in nurses having Bachelor of Science in Nursing Degree is associated with a 9% decrease in patient deaths. Nurse staffing, nurse work environments, and percentages of nurses having Bachelor of Science in Nursing Degree in South Korea are associated with patient mortality. Improving hospital nurse staffing and work environments and increasing the percentages of nurses having Bachelor of Science in Nursing Degree would help reduce the number of preventable in-hospital deaths.